Surface and interface investigation of electrochemically induced corrosion on a quaternary bronze1. (2nd April 2014) - Papadopoulou, O.; Delagrammatikas, M.; Vassiliou, P.; Grassini, S.; Angelini, E.; Gouda, V.; Abel, Marie‐Laure; Rossi, Antonella; Watts, John F.
<x xml:space="preserve">Abstract</x> A quaternary (Cu‐Zn‐Sn‐Pb) cast bronze was submitted to an electrochemical corrosion experiment using an anodic polarization sweep. The surface/interface chemical analysis of the patina removed after the anodic polarization and the metallographic observations on the corroded bulk alloy highlight the onset of a dezincification process followed by a decuprification process, as well as the formation of a Sn‐enriched layer located at the interface patina‐bulk alloy. Different local corrosion patterns, as CuCl precipitation in pits, epitaxial growth of corrosion products on dendritic structures and of Cl‐enriched oxyhydroxides, are observed too. The results are discussed in comparison with experimental findings obtained in previous ageing tests performed on the same alloy in different chloride‐containing solutions. Copyright © 2014 John Wiley & Sons, Ltd.